ҚАРҚАЛПАҚ ХАЛҚЫНЫҢ ЖАҢАДӘРЬЯ ДӘЎИРИНЕ БАЙЛАНЫСЛЫ ТАРИЙХЫЙ ЖЫРЛАРЫ (Таўелибай қарақалпақлары материаллары мысалында) - Қанаатов, Е.Е. (FAN va JAMIYAT, 2020)
The article tells about the historical songs preserved by the Tauelibai Karakalpaks. Such poetic examples that provide information from history are mainly found in the form of termish (short poems dedicated to children). Many of these songs resemble the times and events that provide information about the period when the Karakalpaks lived on the banks of the Janadarya, a huge tributary of the Syr Darya in the XVII-XVIII centuries. Poems written by informants living in the Tauelibay district are new material for Karakalpak folklore. The author indicates that such verses need to be collected more from people and that this may open unknown pages of the history of the Karakalpaks. ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШӘРИЯР» ҲӘМ ОНЫ ҮЙРЕНИЎДИҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ Ш.К.Кеңесбаева - таяныш докторант Әжинияз атындағы Нөкис мәмлекетлик педагогикалық институты Таянч сўзлар: бадиий мерос, «Шарёр» достони, генезиси, жанр хусисияти, тарихий генетик типология, типология ва мил-